A Secure Cloud Storage System Using Attribute Based Encryption Scheme - M, Rekha (IJRDO -Journal of Computer Science Engineering, 2018)
Cloud storage is a progressively popular application of cloud computing which can provide on-demand outsourcing data services for both organizations and individuals. Attribute Based Encryption (ABE) has been widely used in cloud computing where a Data Provider provides outsources of the user encrypted data to a Cloud Service Provider. However, the users may not fully trust the Cloud Service Providers (CSPs). So, the data provider is very difficult to determine whether the CSPs meet their legal expectations for data security or not. Therefore, it is critical to develop efficient auditing techniques to strengthen data owners trust and confidence in cloud storage. An existing work has developed public auditing scheme for secure cloud storage based on the Dynamic Hash Table (DHT). In that, the DHT is a new two-dimensional data structure located at a Third Parity Auditor (TPA) to record the data property information for dynamic auditing. Differing from the existing works, the proposed scheme migrate the authorized information from the CSP to the TPA, and thereby significantly reduces the computational cost and communication overhead. Meanwhile, exploiting the structural advantages of the DHT, the proposed scheme can also achieve higher updating efficiency than the state-of-the-art schemes. In addition, the proposed scheme extends for the purpose of support privacy preservation by combining the authenticator based on the public key with the random masking which is generated by the TPA. Also, the proposed scheme achieves batch auditing by employing the aggregate BLS (Boneh–Lynn–Shacham) signature technique algorithm which is more secure compared to other algorithms. In this way, the proposed work produces the effective results to secure auditing for cloud storage based on the attributes such as computation complexity, storage costs and communication overhead.